Η μετάφραση ως φορέας θεματικών και ιδεολογίας στο πρωτότυπο λογοτεχνικό έργο του Κωνσταντίνου Θεοτόκη - (:unkn) unknown (My University, 2023)
This dissertation examines the literary translations of Konstantin Theotokis (1872-1923), a Corfiot writer, poet and translator. Theotokis translated from many different languages and a wide range of genres. For instance, his work includes excerpts from the Bhagavat Ghita and the Ramayana, plays by Kalidasha, Shakespeare and Aristophanes, poetry by Pindar, Horatius, Catullus, Goethe, Schiller and Heine, short texts by Dostoyevsky, Tolstoy, Turgenev and Gorki, ancient Greek and Latin philosophy (Plato, Vergil, Lucretius), Gustav Flaubert’s Madame Bovary. Theotokis also produced ample original literary work, much of which holds a significant place in modern Greek literature. The fact that his translations comprise more than half of the total bulk of his writings, and cover the whole period of his life and work as an author, indicates that he viewed translation as a process parallel with literary writing and vital to it. Although he is traditionally considered as a naturalist, his work also bears influences from romanticism, Indian literature and philosophy, ancient Greek and Latin poets and so on, so it is evident that he has drawn inspiration from the texts he translated. In my thesis, apart from examining the choices Theotokis made in his translations (in terms of language, metre, style etc.), I also demonstrate how they formed his literary identity and how they served as a means of introducing certain themes and ideological elements into modern Greek literature. In addition, the thesis discusses Theotokis’ affiliation to the Heptanesian School and his ideological and literary kinship with Dionysios Solomos, the national poet of Greece. Finally, an important aspect of this dissertation is that it explores the use of the demotic Greek by Theotokis, his attitude towards the Language Issue and his linguistic theory.
Keywords: Κωνσταντίνος Θεοτόκης, Μετάφραση, Μεταφρασιολογία, Νεοελληνική Λογοτεχνία, Επτανησιακή Σχολή, Γλωσσικό ζήτημα, Ρομαντισμός, Ιδεαλισμός, Ρεαλισμός, Νατουραλισμός, Υλισμός; Konstantin Theotokis, Translation, Translation Theory, Modern Greek Literature, Heptanesian School, Language Issue, Romanticism, Idealism, Realism, Naturalism, Materialism